Intervention Project to Improve Cognitive Performance in Patients with Mild Cognitive Impairment - de Sousa, Pedro Miguel; Ferreira, Joana M.; Conde Gonçalves, Pedro; Fonseca, Maria João; Seixas, Miguel; Videira, Inês; Balsa, Maria João; Christel Sá, Márcia (Gazeta Médica, 2023)
INTRODUCTION: In 2018, an observational study developed at a Portuguese Primary Care Health Unit estimated a mild cognitive impairment (MCI) prevalence of 29.1%, with an association between better performance in Montreal Cognitive Assessement (MoCA) test and reading of newspapers and books or hobbies. The objective of the present project was to improve the cognitive capacity of the elderly with MCI through cognitive training activities. METHODS: We conducted an intervention project in a Primary Care Health Unit, with a sample of 20 elderly with MCI. Cognitive training sessions took place with delivery of homework exercise books. The Portuguese version of MoCA was applied at zero, three and six months to evaluate cognitive performance. RESULTS: At the beginning of the study, the median MoCA score was 18.5. After six months, a median score of 23 was observed. There was an improvement in the global score at all cognitive domains except language and orientation. CONCLUSION: The cognitive performance improved after the six months period achieving our purpose. Cognitive training has a potential beneficial effect on the health of the elderly population and requires simple, low-cost materials that can be applied in nursing homes and day care centers through caregivers.